Post-storm fine-particle deposition and heavy-metal enrichment in a surface event layer of the northeastern Beibu Gulf after Super Typhoon Yagi - Haidong Li; Yunpeng Lin; Yunhai Li; Hengbo Wang; Shanshan Zhang; Hannv Zhang; Guicai Zhong; Jinlong Wang; Fanyu Lin (Frontiers in Marine Science, 2026)
Storm-generated surface deposits can preserve short-lived sedimentary and geochemical signals, but their interpretation requires careful distinction between event-layer contrasts and true pre–post storm changes. Here we examine the sedimentary and heavy-metal characteristics of a post-storm surface drape and the underlying reference sediment in the northeastern Beibu Gulf after Super Typhoon Yagi. Grain size, total organic carbon (TOC), aluminum (Al), and heavy metal concentrations were analyzed, and interlayer differences were evaluated using correlation analysis and a Surface–Subsurface Contrast Index (SSCI). Because sediment samples were collected 20–21 days after Typhoon Yagi and no directly observed pre-typhoon surface baseline was available, the observed differences are interpreted as post-event surface–subsurface contrasts rather than direct pre–post storm concentration changes. The surface drape is laterally persistent, finer grained, and enriched in TOC and Al, indicating that it primarily records post-storm settling of fine particles rather than deposition under peak storm energy. Most metals, including V, Cr, Co, Ni, Zn, Pb, Mn, and As, show higher concentrations in the surface drape than in the subsurface reference layer, with mean surface–subsurface contrasts of 35–61%, whereas Cu shows only a limited contrast and Cd remains broadly unchanged. V, Cr, Co, Ni, Zn, and Pb exhibit spatially coherent high-value zones in the surface drape, broadly consistent with the distribution of fine-grained and Al-rich sediments. These contrasts suggest that the post-storm surface drape preferentially preserved fine-grained, Al-rich, and organic-bearing particles that acted as metal carriers. Our results highlight that post-storm surface sediments in tropical–subtropical bays should be interpreted as event-layer archives of short-term sedimentary and geochemical reworking rather than as simple indicators of long-term background seabed conditions. These findings provide insight into how extreme storms may imprint short-term source-to-sink signals in coastal event deposits.